Pengaruh Keberagaman Masyarakat Terhadap Pengambilan Keputusan: Studi Kasus Pemerintah Desa Panjangejo - Priyanto, Agus; Rahmat, Al Fauzi; Pora, Sahrul; Ari Sandi, Fadri (Nakhoda: Jurnal Ilmu Pemerintahan, 2025)
Village governance in Indonesia has received special attention following the enactment of Law No. 6 of 2014, which grants significant authority and responsibilities to village governments. This study aims to explore how the Panjangrejo Village Government engages its diverse community in the decision-making process. A descriptive qualitative method was employed, with primary data collected through interviews with village officials, residents, and community leaders. The findings indicate that the Panjangrejo Village Government, considering the diversity of its members, involves the community through representatives such as local community leaders and the Village Consultative Body (BPD) in decision-making. Additionally, the decision-making process follows a hierarchical approach, starting with village discussions at the hamlet level and continuing up to the village-level meetings (Musdes). This bottom-up approach has been practiced for several years. The Panjangrejo Village Government prioritizes the needs of the village and applies participatory principles in every decision made. This study highlights the importance of community participation in village governance to enhance the effectiveness of decision-making that accommodates diversity.